Sketches [compact disc] - MacMaster, Natalie; MacMaster, Natalie (Linus Entertainment, 2019)
Superstar in the Celtic music world, Natalie MacMaster has built a career on electrifying playing and innovative recordings that stretched the world music genre into contemporary commercial acceptance. After eight years without a solo album, MacMaster returned to the studio to record a new solo album. The result is a fiery collection of traditional tunes and medleys mixed with new compositions teeming with retrospect and legacy as she looks back on the journey of her life and career.